TEACHERS' RESPONSE TOWARD STUDENTS’ MISBEHAVIOR IN THE TEACHING LEARNING PROCESS - Sevrika, Hevriani; Merina, Yola (Universitas PGRI Sumatera Barat, 2019)
Abstract This research has purpose to find out how English teachers respond towards students misbehavior. The writers used two instruments in gotten the data which were observation checklist, video and field note. The sample was two English teachers who taught at VIII grade of Junior high school in Padang. Writers wanted to know how English teachers respond to passive and active misbehavior that has been done by the students in the teaching learning process. The data were the participants which are teacher 1 and teacher 2 used serious and minor respond toward students’ misbehavior. In the students’ passive misbehavior they used difference respond. Teacher 1 used serious respond and teacher 2 used minor response. Then, in the active students’ misbehavior both of the teachers used serious responds.